Aphasia and herpes virus encephalitis: a case study - Soares-Ishigaki, Ellen Cristina Siqueira; Cera, Maysa Luchesi; Pieri, Alexandre; Ortiz, Karin Zazo (São Paulo Medical Journal, 2012)
CONTEXT: Meningoencephalitis early in life, of any etiology, is a risk factor for development of subsequent sequelae, which may be of physical, psychiatric, behavioral or cognitive origin. Anomia is a language abnormality frequently found in such cases, and other language deficits are rarely described. The aim of this study was to describe the cognitive and linguistic manifestations following a case of herpetic meningoencephalitis in a 13-year-old patient with eight years of schooling. CASE REPORT: The patient underwent a speech-language audiology assessment nine months after the neurological diagnosis. The battery of tests included the Montreal-Toulouse Language Assessment test protocol (MT Beta-86, modified), the description from the Cookie Theft task of the Boston Diagnostic Aphasia Examination (BDAE), an informal assessment of the patient’s logical and mathematical reasoning, and the neuropsychological subtests from the WAIS-III scale, which assess working memory. The patient presented mixed aphasia, impairment of short-term memory and working memory, and dyscalculia. This case also presented severe cognitive and linguistic deficits. Prompt diagnosis is crucial, in order to enable timely treatment and rehabilitation of this neurological infection and minimize the cognitive deficits caused by the disease.